Determining knowledge, attitudes, and practices on food waste management among Health Sciences students in Universiti Teknologi MARA / Nor Juliana Abdul Jalil ... [et al.] - Abdul Jalil, Nor Juliana; Mohd Yatim, Siti Rohana; Wan Rasdi, Nadiah; Farizan, Nor Hamzani; Md Rashid, Razi Ikhwan; Megat Mokhtar, Megat Azman; Abdullah, Samsuri (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
This study aims to determine food waste management among students in Universiti Teknologi MaraUiTM). The information was collected by using a questionnaire comprising four sections: demographic information, knowledge, attitude and practice on food waste. The number of respondents involved was 201. The finding showed that the students have a high level of knowledge (3.935 ± 0.9699), attitude (5.100 ± 0.9798) and practice (2.672 ± 0.8897) towards food waste management. There was a positive significant correlation between knowledge with attitude (rs = 0.217, p = 0.02), and attitude with practice (rs = 0.241, p = 0.01). However, the correlation of knowledge with practice (rs = 0.073, p = 0.31) was not statistically correlated. There was a significant association between knowledge with gender (rs = 14.800, p = 0.011), and attitude with gender (rs = 15.449, p = 0.009) meanwhile there was no significant association between practice and gender (rs = 8.900, p = 0.064). Furthermore, there was no significant association between knowledge with income (rs = 15.025, p = 0.131), attitude with income (rs = 9.381, p = 0.496), and practice with income (rs, 9.054, p = 0.338). Hence, the results suggest that to change people's behaviour in waste management, the knowledge and awareness in waste management must be improved sustainably so that it will change a person's attitude and form it into positive action.